(untitled) (Bangladesh Agronomy Journal, 2021)
Field experiments were conducted at Multi Location Testing (MLT) sites of Chandina and Debidwer of Cumilla district, and Kasba of Brahmanbaria district under on-farm research division (OFRD), Bangladesh Agricultural Research Institute, Cumilla during 2016-18 to find out the appropriate dose of fertilizer for the maximum productivity of hybrid cauliflower varieties. Five integrated nutrient management packages such as T1= Recommended fertilizer dose for high yield goal (HYG), viz. 40-20-38-7-0-0 NPKSZnB Kg ha-1, T2= T1 + 1.5 t ha-1 vermicompost, T3 = T1 + 5 t ha-1 cowdung, T4= STB (107-61-107-30-3.0-1.0 NPKSZnB Kg ha-1 and T5= Farmers practices (114-74-123.5-0-0 NPKSZnB Kg ha-1) were used in the trial. The experiment was laid out in a Randomized Complete Block (RCB) design with six dispersed replications. The result revealed that the highest curd breadth (21.68 cm), individual curd weight (1.86 Kg) and curd yield (44.14 t ha-1) was obtained from T2 treatment followed by T3 and T4 treatments. The lowest yield was found from farmers practice. Similarly the highest gross return (Tk. 626669.00 ha-1) and gross margin (Tk. 493869.00 ha-1) were also found from T2 treatment and the lowest (Tk. 457734.00 ha-1 and 438066.00 ha-1) respectively from farmer’s practice T5. Bangladesh Agron. J. 2020, 23(2): 45-49